A high thermal conductivity shaped phase change material and preparation method thereof
By using a cladding material made of bacterial cellulose and expanded graphite to coat the phase change substrate, the problem of easy flow out of the thermal phase change material when liquid is solved, and the thermal conductivity is improved, making it suitable for applications with high thermal conductivity requirements.
Patent Information
- Application Number
- CN202211021532.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-24
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-08-24
AI Technical Summary
Existing thermally conductive phase change materials are prone to flow out in liquid state, and have insufficient thermal conductivity, making it difficult to meet the application of high thermal conductivity requirements.
The phase change substrate is coated with a cladding material made of bacterial cellulose and expanded graphite to form a highly thermally-conductive phase change material. Bacterial cellulose provides support and three-dimensional interpenetrating network structure, and expanded graphite improves the thermal conductivity and elasticity of the material.
It effectively avoids the outflow problem of phase-changing substrate in liquid state, and significantly improves the thermal conductivity of the material, and is suitable for applications with high thermal conductivity requirements.
Smart Images

Figure BDA0003814363210000081 
Figure BDA0003814363210000082 
Figure BDA0003814363210000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thermal conductive phase change materials, and in particular to a high thermal conductive shaped phase change material and a preparation method thereof. Background Art
[0002] Thermally conductive phase change materials utilize their solid-liquid phase change characteristics and improve the thermal conductivity of phase change thermal interface materials through the modification of high thermal conductivity fillers to achieve thermal management functions. The advantages of thermally conductive phase change materials are that they are solid at room temperature and can be made into gaskets for easy assembly, without the easy contamination of thermal grease. When working, they can obtain low interfacial thermal resistance similar to that of thermal grease, and are usually used as a substitute for thermal grease. However, phase change materials are not suitable for electronic products that require insulation, and there is a possibility of flowing out from the interface when melted into liquid.
[0003] In order to solve the problem that the thermal conductive phase change material is easy to flow out when in liquid state, some microcapsule phase change interface materials and fixed phase change interface materials have appeared on the market. Phase change material microcapsules are composite phase change materials with core-shell structure formed by coating a layer of stable shell layer on the surface of phase change substrate using microcapsule technology. However, organic phase change materials prepared by microcapsule encapsulation technology usually have poor heat storage capacity of shell materials, which will lead to lower latent heat storage density of encapsulated materials than those without encapsulated materials; fixed phase change materials are phase change materials that are coated by blending, melting, porous adsorption and other methods. Compared with microcapsule phase change materials, fixed phase change materials have good thermal conductivity and high coverage rate. However, for some application projects with relatively high thermal conductivity requirements, the thermal conductivity of existing fixed phase change materials needs to be further improved. Summary of the invention
[0004] The main purpose of the present invention is to provide a high thermal conductivity fixed phase change material and a preparation method thereof, aiming to provide a thermally conductive phase change material that is not easy to flow out in liquid state and has high thermal conductivity.
[0005] To achieve the above-mentioned purpose, the high thermal conductivity shaped phase change material proposed in the present invention comprises a phase change substrate and a coating material coating the phase change substrate, wherein the weight ratio of the phase change substrate to the coating material is (1:0.1)-(1:1); wherein,
[0006] The phase change substrate comprises the following components in parts by weight: a resin matrix, 100 to 150 parts; a thermal conductive filler, 450 to 600 parts; and a coupling agent, 5 to 12 parts.
[0007] The coating material has a three-dimensional interpenetrating network structure, and comprises the following components in mass fractions: bacterial cellulose, 100-150 parts; expanded graphite, 10-50 parts.
[0008] In one embodiment, the bacterial cellulose is synthesized by one or more microorganisms of the genera Bacillus, Gluconacetobacter, and Acetobacter.
[0009] In one embodiment, the bacterial cellulose is nanobacterial cellulose.
[0010] In one embodiment, the thermally conductive filler is selected from one or more of silver powder, aluminum powder, copper powder, aluminum oxide, aluminum nitride, boron nitride, silicon nitride, zinc oxide, beryllium oxide, silicon dioxide, graphite, graphene, carbon nanotubes, and carbon fibers.
[0011] In one embodiment, the thermally conductive filler includes boron nitride, and the phase change substrate further includes polyimide.
[0012] In one embodiment, the phase change substrate further comprises one or more of the following components in weight fractions: flame retardant, 30 to 100 parts; tackifier, 10 to 20 parts; anti-aging agent, 1 to 10 parts; antioxidant, 1 to 10 parts.
[0013] In one embodiment, the flame retardant is selected from one or more of aluminum hydroxide, melamine phosphate and polyphosphate.
[0014] In one embodiment, the tackifier is selected from one or more of hydrogenated rosin resin, C9 petroleum resin, C5 petroleum resin, and microcrystalline wax.
[0015] In one embodiment, the resin matrix is selected from paraffin and / or modified paraffin.
[0016] The present invention also provides a method for preparing the above-mentioned high thermal conductivity fixed phase change material, comprising the following steps:
[0017] S1: adding the resin matrix, the thermal conductive filler and the coupling agent into a reaction kettle to prepare the phase change substrate;
[0018] S2: adding the bacterial cellulose and the expanded graphite into another reaction kettle to prepare a coating material;
[0019] S3: using the coating material prepared in S2 to coat the phase change substrate prepared in S1.
[0020] The technical solution of the present invention uses a coating material made of bacterial cellulose and expanded graphite to coat the phase change substrate, which not only avoids the leakage of the phase change substrate when it is in liquid state, but also improves the thermal conductivity of the phase change substrate. In the present invention, the bacterial cellulose provides a support frame for the phase change substrate. Since the bacterial cellulose has a high degree of polymerization, an ultra-fine three-dimensional interpenetrating network structure is formed. On the one hand, its interlaced internal network structure shows a continuous and compact form on a macro scale, and can still remain intact under the seepage impact of the phase change substrate. The particles are highly correlated, providing a structural foundation of a certain strength for adsorbing the phase change substrate, avoiding the leakage of the phase change substrate when it is in liquid state. On the other hand, the three-dimensional interpenetrating network structure also provides a large number of evenly distributed channels for the diffusion of the phase change substrate, and since the channels are interconnected, a smooth heat conduction path is formed inside the high thermal conductivity fixed phase change material, thereby making the present invention The thermal conductivity of the thermally conductive phase change composite material is enhanced; in addition, bacterial cellulose also has the advantages of high tensile strength, biocompatibility, adaptability and biodegradability. High tensile strength and good biocompatibility can enhance the structural stability of the thermally conductive phase change composite material, and biodegradability makes the thermally conductive phase change composite material of the present invention removable; in order to further improve the thermal conductivity of the high thermal conductivity fixed phase change material of the present invention, the present invention also modifies the bacterial cellulose by adding expanded graphite so that the coating material has a certain elasticity. Compared with rigid materials, the phase change substrate can obtain a larger heat conduction area when flowing in the flexible material, so that the thermal conductivity of the high thermal conductivity fixed phase change material of the present invention is further improved. DETAILED DESCRIPTION
[0021] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art. Unless otherwise specified, the meanings of the terms in this specification are the same as those generally understood by those skilled in the art, but in case of conflict, the definitions in this specification shall prevail.
[0022] As used herein, "includes," "comprising," "including," "containing," "having," or other variations are intended to encompass non-exclusive inclusions, and no distinction is made between these terms. The term "comprising" means that other steps and ingredients that do not affect the end result may be added. The term "comprising" also includes the terms "consisting mainly of" and "consisting essentially of." The compositions and methods / processes of the present invention comprise, consist of, and consist essentially of the essential elements and limitations described herein, as well as any additional or optional ingredients, components, steps, or limitations described herein.
[0023] All numerical values or expressions related to component amounts, process conditions, etc. used in the specification and claims should be understood to be modified by "about" in all cases. All ranges related to the same component or property include endpoints, which can be independently combined. Since these ranges are continuous, they are included in each numerical value between the minimum and maximum values. It should also be understood that any numerical range quoted in the present application is expected to include all sub-ranges within the range. As used herein, "weight parts", "weight parts", "mass parts" or "mass parts" are used interchangeably, and the weight parts can be any fixed weight (such as 1mg, 1g, 2g, 5g, or 1kg, etc.) expressed in milligrams, grams or kilograms. For example, a composition consisting of 1 weight part component a and 9 weight parts component b can be 1 gram component a+9 grams component b, or it can be a composition consisting of 10 grams component a+90 grams component b, etc.
[0024] In addition, if the meaning of "and / or" appears in the full text is to include three parallel solutions, taking "A and / or B" as an example, it includes solution A, solution B, or a solution that satisfies both A and B. The technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.
[0025] Phase change materials have defects such as easy leakage, low thermal conductivity, and volume thermal expansion during application. Material leakage will affect the stability of the equipment and the reliability of the system. Too low thermal conductivity will affect the heat transfer performance of the phase change material and reduce its energy storage effect in application. Volume expansion will cause the system pressure to increase and the heat transfer surface to be insufficiently contacted, thus reducing the heat transfer performance. After research, the inventors found that studying porous skeleton composite phase change materials with stable structure and excellent thermal performance is an effective way to improve.
[0026] Therefore, the present invention proposes a high thermal conductivity shaped phase change material, which includes a phase change substrate and a coating material coating the phase change substrate, and the weight ratio of the phase change substrate to the coating material is (1:0.1)-(1:1); wherein the phase change substrate includes the following components in weight: a resin matrix, 100 to 150 parts; a thermal conductive filler, 450 to 600 parts; a coupling agent, 5 to 12 parts; the coating material has a three-dimensional interpenetrating network structure, and the coating material includes the following components in mass fractions: bacterial cellulose, 100-150 parts; and expanded graphite, 10-50 parts.
[0027] The resin matrix is selected from paraffin and / or modified paraffin, wherein the modified paraffin can be one or more of hydrogenated modified wax powder, pinene resin modified wax and pentaerythritol ester modified wax.
[0028] Among them, the weight ratio of the phase change substrate to the coating material can be 1:0.1, 1:0.5, 1:1 or any value therebetween; in the components of the phase change substrate, the weight ratio of the resin matrix can be 100 parts, 125 parts, 150 parts or any value therebetween, and the weight ratio of the thermal conductive filler can be 450 parts, 500 parts, 600 parts or any value therebetween; in the components of the coating material, the weight fraction of the bacterial cellulose can be 100 parts, 125 parts, 150 parts or any value therebetween, and the weight ratio of the expanded graphite can be 10 parts, 25 parts, 50 parts or any value therebetween.
[0029] The technical solution of the present invention uses a coating material made of bacterial cellulose and expanded graphite to coat the phase change substrate, which not only avoids the leakage of the phase change substrate when it is in liquid state, but also improves the thermal conductivity of the phase change substrate. In the present invention, the bacterial cellulose provides a support frame for the phase change substrate. Since the bacterial cellulose has a high degree of polymerization, an ultra-fine three-dimensional interpenetrating network structure is formed. On the one hand, its interlaced internal network structure shows a continuous and compact form on a macro scale, and can still remain intact under the seepage impact of the phase change substrate. The particles are highly correlated, providing a structural foundation of a certain strength for adsorbing the phase change substrate, avoiding the leakage of the phase change substrate when it is in liquid state. On the other hand, the three-dimensional interpenetrating network structure also provides a large number of evenly distributed channels for the diffusion of the phase change substrate, and since the channels are interconnected, a smooth heat conduction path is formed inside the high thermal conductivity fixed phase change material, thereby making the present invention The thermal conductivity of the thermally conductive phase change composite material is enhanced; in addition, bacterial cellulose also has the advantages of high tensile strength, biocompatibility, adaptability and biodegradability. High tensile strength and good biocompatibility can enhance the structural stability of the thermally conductive phase change composite material, and biodegradability makes the thermally conductive phase change composite material of the present invention removable; in order to further improve the thermal conductivity of the high thermal conductivity fixed phase change material of the present invention, the present invention also modifies the bacterial cellulose by adding expanded graphite so that the coating material has a certain elasticity. Compared with rigid materials, the phase change substrate can obtain a larger heat conduction area when flowing in the flexible material, so that the thermal conductivity of the high thermal conductivity fixed phase change material of the present invention is further improved.
[0030] Bacterial cellulose (BC) is a porous network biopolymer derived from microbial fermentation synthesis, produced by one or more microorganisms, such as Achromobacter, Alcaligenes, Aerobacter, Agrobacterium, Azotobacter, Saccharoacetobacter, Pseudomonas, Rhizobium, Sarcina, Soft Rot Fungus, Rhodobacter, Serratia and Lactobacillus, Bacillus hansenii and Bacillus intermedia, etc. According to the high thermal conductivity setting phase change material of the present invention, the bacterial cellulose is synthesized by one or more microorganisms of the genera Bacillus, Gluconacetobacter and Acetobacter, and the cellulose yield of these microorganisms is higher than that of other microorganisms.
[0031] According to the high thermal conductivity phase change composite material of the present invention, the bacterial cellulose is nano bacterial cellulose. Compared with ordinary bacterial cellulose, nano bacterial fiber has a larger surface area and can form hydrogen bonds, so that the material has a stronger and denser network structure, thereby greatly improving the barrier properties of the material, further reducing the possibility of leakage of the phase change substrate and improving the thermal conductivity of the high thermal conductivity phase change composite material of the present invention. Nano bacterial cellulose is easy to be compounded with other materials to obtain a coating material composed of nano bacterial cellulose and expanded graphite with adjustable properties.
[0032] According to the high thermal conductivity shaped phase change material of the present invention, the thermal conductive filler is selected from one or more of silver powder, aluminum powder, copper powder, aluminum oxide, aluminum nitride, boron nitride, silicon nitride, zinc oxide, beryllium oxide, silicon dioxide, graphite, graphene, carbon nanotubes, and carbon fibers.
[0033] According to the high thermal conductivity shaped phase change material of the present invention, the thermal conductive filler includes boron nitride, and the phase change substrate also includes polyimide. Studies have found that boron nitride and polyimide have a synergistic effect. Compared with using boron nitride or polyimide alone to improve the thermal conductivity of the phase change substrate, using boron nitride and polyimide at the same time can more significantly improve the thermal conductivity of the phase change substrate.
[0034] According to the high thermal conductivity setting phase change material of the present invention, the phase change substrate further comprises one or more of the following components in weight fractions: flame retardant, 30 to 100 parts; tackifier, 10 to 20 parts; anti-aging agent, 1 to 10 parts; antioxidant, 1 to 10 parts. That is, the weight fraction of the flame retardant can be 30 parts, 50 parts, 100 parts or any value therebetween; the weight fraction of the tackifier can be 10 parts, 15 parts, 20 parts or any value therebetween; the weight fraction of the anti-aging agent can be 1 part, 5 parts, 10 parts or any value therebetween; the weight fraction of the antioxidant can be 1 part, 5 parts, 10 parts or any value therebetween; the weight fraction of the antioxidant can be 1 part, 5 parts, 10 parts or any value therebetween.
[0035] According to the high thermal conductivity setting phase change material of the present invention, the flame retardant is selected from one or more of aluminum hydroxide, melamine phosphate and polyphosphate.
[0036] According to the high thermal conductivity setting phase change material of the present invention, the tackifier is selected from one or more of hydrogenated rosin resin, C9 petroleum resin, C5 petroleum resin and microcrystalline wax.
[0037] According to the high thermal conductivity shaping phase change material of the present invention, the coupling agent is selected from one or more of a titanate coupling agent, a zirconate coupling agent and a silane coupling agent, wherein the silane coupling agent may be KH550 and / or KH570.
[0038] According to the high thermal conductivity setting phase change material of the present invention, the anti-aging agent is selected from one or more of 2,8-di-tert-butyl-4-methylphenol, butylated hydroxyanisole, tert-butylhydroquinone and butylated hydroxytoluene.
[0039] According to the high thermal conductivity setting phase change material of the present invention, the antioxidant is selected from one or more of 2,2-methylenebis(4-methyl-6-tert-butylphenol), 2,6-tert-butyl-4-methylphenol, pentaerythritol tetrakis(β-(3,5-tert-butyl-4-hydroxyphenyl)propionate), and tetraphenyl dipropylene glycol diphosphite.
[0040] The present invention also provides a method for preparing the above-mentioned high thermal conductivity fixed phase change material, comprising the following steps:
[0041] S1: adding the resin matrix, the thermal conductive filler and the coupling agent into a reaction kettle to prepare the phase change substrate;
[0042] S2: adding the bacterial cellulose and the expanded graphite into another reaction kettle to prepare a coating material;
[0043] S3: using the coating material prepared in S2 to coat the phase change substrate prepared in S1.
[0044] More specifically, in one reactor, 100-150 parts by weight of a resin matrix, 450-600 parts by weight of a thermal conductive filler, 5-12 parts by weight of a coupling agent, 30-100 parts by weight of a flame retardant, 10-20 parts by weight of a tackifier, 1-10 parts by weight of an anti-aging agent, and 1-10 parts by weight of an antioxidant are added, and a solvent is added, and the mixture is heated to 50° C.-90° C. and stirred magnetically for 1-2 hours to obtain a phase change substrate for standby use; in another reactor, 100-150 parts by weight of bacterial cellulose and 1 0-50 parts of expanded graphite are added with a solvent, heated to 50°C-90°C, and stirred under ultrasound and magnetic force for 3-6 hours to obtain a coating material for standby use; in another reaction kettle, a standby phase change substrate and a coating material are added, wherein the weight ratio of the phase change substrate to the coating material is (1:0.1)-(1:1), and stirred at high speed at 50°C-90°C for 1-2 hours, cooled and allowed to stand, and then separated, washed and dried to obtain the high thermal conductivity fixed phase change material of the present invention.
[0045] The following is a further clear and complete description of the technical features of the technical solution provided by the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] Example 1
[0047] formula
[0048]
[0049]
[0050] Preparation steps
[0051] S1: In a reaction kettle, add 100 parts by weight of paraffin wax, 300 parts of boron nitride, 300 parts of carbon fiber, 12 parts of KH550, 50 parts of flame retardant, 20 parts of tackifier, 3 parts of anti-aging agent and 8 parts of antioxidant, add solvent, heat to 60°C, stir magnetically for 1-2 hours, and obtain a phase change substrate for standby use;
[0052] S2: In another reaction kettle, add 100 parts of bacterial cellulose and 50 parts of expanded graphite, add solvent, heat to 60°C, and stir under ultrasound and magnetic force for 3-6 hours to obtain a coating material for standby use;
[0053] S3: In another reaction kettle, add 100 parts of the reserved phase change substrate and 10 parts of the coating material, stir at high speed at 60°C for 1-2 hours, cool and stand for stratification, separate, wash and dry to obtain a high thermal conductivity fixed phase change material.
[0054] Example 2
[0055] formula
[0056]
[0057] Preparation steps
[0058] Except that the weight fraction of the coating material added in S3 is 100 parts, the remaining steps are the same as those in Example 1.
[0059] Example 3
[0060] formula
[0061]
[0062] Preparation steps
[0063] Except that the weight fraction of bacterial cellulose added in S2 is 150 parts and the weight fraction of expanded graphite is 10 parts, the remaining steps are the same as those in Example 1.
[0064] Example 4
[0065] formula
[0066]
[0067] Preparation steps
[0068] Except that the weight portion of KH550 added in S1 is 5 parts, the remaining steps are the same as those in Example 1.
[0069] Example 5
[0070] formula
[0071]
[0072] Preparation steps
[0073] Except that the carbon fiber added in S1 is replaced by polyimide, the remaining steps are the same as those in Example 1.
[0074] Example 6
[0075] formula
[0076]
[0077] Preparation steps
[0078] Except that the thermal conductive filler added in S1 is 450 parts of carbon fiber, the remaining steps are the same as those in Example 1.
[0079] Comparative Example 1
[0080] formula
[0081]
[0082] Preparation steps
[0083] Except that the coating material in S2 does not include expanded graphite, the remaining steps are the same as those in Example 1.
[0084] Comparative Example 2
[0085] formula
[0086]
[0087]
[0088] Preparation steps
[0089] Except that the coating material in S2 does not include bacterial cellulose, the remaining steps are the same as those in Example 1.
[0090] Comparative Example 3
[0091] formula
[0092]
[0093] Preparation steps
[0094] Except that all carbon fibers in S1 are replaced by polyimide, the remaining steps are the same as those in Example 6.
[0095] Performance Testing
[0096] The thermal conductivity of Examples 1-6 and Comparative Examples 1-3 was tested, and the results are shown in the following table:
[0097]
[0098]
[0099] Referring to the above table, by comparing Example 1 with Comparative Example 1 and Comparative Example 3, it can be seen that bacterial cellulose and expanded graphite synergistically improve the thermal conductivity of the high thermal conductivity fixed phase change material of the present invention. By comparing Examples 4-6 with Comparative Example 3, it can be seen that boron nitride and polyimide can synergistically improve the thermal conductivity of the high thermal conductivity fixed phase change material of the present invention.
[0100] The foregoing examples are merely illustrative and are used to explain some features of the method of the present invention. The appended claims are intended to claim the widest possible range that can be conceived, and the embodiments presented herein are only illustrations of selected implementations according to the combination of all possible embodiments. Therefore, it is the applicant's intention that the appended claims are not limited by the selection of examples that illustrate the features of the present invention. Some numerical ranges used in the claims also include sub-ranges within them, and changes in these ranges should also be interpreted as being covered by the appended claims where possible.
Claims
1. A high thermal conductivity shaped phase change material, characterized in that: It comprises a phase change substrate and a coating material coating the phase change substrate, wherein the weight ratio of the phase change substrate to the coating material is (1:0.1)-(1:1); wherein, The phase change substrate comprises the following components in parts by weight: a resin matrix, 100 to 150 parts; a thermal conductive filler, 450 to 600 parts; and a coupling agent, 5 to 12 parts. The coating material has a three-dimensional interpenetrating network structure, and the coating material comprises the following components in mass fractions: bacterial cellulose, 100-150 parts; expanded graphite, 10-50 parts; The covering material is elastic.
2. The high thermal conductivity shaped phase change material according to claim 1, characterized in that: The bacterial cellulose is synthesized by one or more microorganisms of the genera Bacillus, Gluconacetobacter and Acetobacter.
3. The high thermal conductivity shaped phase change material according to claim 2, characterized in that: The bacterial cellulose is nano bacterial cellulose.
4. The high thermal conductivity shaped phase change material according to claim 1, characterized in that: The thermally conductive filler is selected from one or more of silver powder, aluminum powder, copper powder, aluminum oxide, aluminum nitride, boron nitride, silicon nitride, zinc oxide, beryllium oxide, silicon dioxide, graphite, graphene, carbon nanotubes, and carbon fibers.
5. The high thermal conductivity shaped phase change material according to claim 4, characterized in that: The thermal conductive filler includes boron nitride, and the phase change substrate further includes polyimide.
6. The high thermal conductivity shaped phase change material according to claim 1, characterized in that: The phase change substrate further comprises one or more of the following components in weight fractions: flame retardant, 30 to 100 parts; tackifier, 10 to 20 parts; anti-aging agent, 1 to 10 parts; antioxidant, 1 to 10 parts.
7. The high thermal conductivity shaped phase change material according to claim 6, characterized in that: The flame retardant is selected from one or more of aluminum hydroxide, melamine phosphate and polyphosphate.
8. The high thermal conductivity shaped phase change material according to claim 6, characterized in that: The tackifier is selected from one or more of hydrogenated rosin resin, C9 petroleum resin, C5 petroleum resin and microcrystalline wax.
9. The high thermal conductivity shaped phase change material according to any one of claims 1 to 8, characterized in that: The resin matrix is selected from paraffin and / or modified paraffin.
10. A method for preparing a high thermal conductivity shaped phase change material according to any one of claims 1 to 9, characterized in that: The steps include: S1: adding the resin matrix, the thermal conductive filler and the coupling agent into a reaction kettle to prepare the phase change substrate; S2: adding the bacterial cellulose and the expanded graphite into another reaction kettle to prepare a coating material; S3: using the coating material prepared in S2 to coat the phase change substrate prepared in S1.
Citation Information
Patent Citations
Heat conducting phase change material and preparation method thereof
CN106753263A
Temperature-resistant heat-conduction phase-change material and preparation method thereof
CN108003406A
Removable thermal-conductive phase change material and preparation method thereof
CN108102376A
Boron nitride / cellulose encapsulated thermal-conductivity-enhanced formalized phase-change material
CN110746937A